The Influence Of E-Customer Satisfaction, E-Service Quality And Sales Promotion On E-Customer Loyalty Of Tokopedia Customers - Balla Wahyu Budiarto; Putri Ekaresty Haes; Winanto Nawarcono; Ainil Mardiah; Tri Apriyono (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
The competition between online firms occasionally gets more intense due to Indonesia's growing use of the digital economy. The context of this study is competition that attempts to boost customer loyalty through excellent service and alluring promos. This study uses e-customer satisfaction as an intermediary variable in Tokopedia's e-commerce to examine the impact of e-service quality and sales promotion on e-customer loyalty. Using non-probability sampling strategies and purposive sampling approaches on 100 respondents. SEM-PLS, or structural equation modeling, is the analytical technique employed. This study discovered that e-service quality and sales promotion have a direct effect on e-customer satisfaction, e-customer satisfaction has no indirect effect on e-customer loyalty, and e-service quality and sales promotion have no effect on e-customer loyalty with e-customer satisfaction as an intervening variable.